Pengaruh Kompetensi SDM, Moralitas Individu, Dan Sistem Pengendalian Internal Terhadap Pencegahan Fraud: Studi Empiris Pada Kelurahan Yang Tercatat Di Kecamatan Bantargebang Kota Bekasi - Komalasari, Tika; Annisa, Dea (Institut Bisnis dan Informatika Kesatuan, 2023)
The purpose of this research is to examine and explain the influence of SDM competence, morality individual and internal control systems on fraud prevention. his research is a quantitative study with a descriptive research design. The data source in this study uses primary data obtained from the results of the distribution of questionnaires to all officials in the village recorded in Bantargebang District of 45 respondents. This research was conducted in Bantargebang Village, Cikiwul Village, Ciketing udik village and sumur batu village. The results of this study indicate that SDM competence, morality individual, and internal control systems, have a significant simultaneous effect on fraud prevention. partially, the SDM competence has no effect on fraud prevention, morality individual has an effect on fraud prevention and internal control system has no effect on fraud prevention. Keywords: SDM Competence, Morality individual, internal control system, fraud prevention